The dark wives [large type] - Cleeves, Ann (Cleeves, Ann. Vera Stanhope series., 2024)
A body is found by an early morning dog walker on the common outside Rosebank, a care home for troubled teens. The victim is Josh, a staff member, who never showed up to work. DI Vera Stanhope is called out to investigate. Her only clue is the disappearance of 14-year-old resident Chloe. Vera can't bring herself to believe that a teenager is responsible for the murder, but even she can't dismiss the possibility. Vera, Joe and new team member Rosie are soon embroiled in the case, but when a second body is found near the Three Dark Wives standing stones in the wilds of the Northumbrian countryside, folklore and fact begin to collide. Vera knows she has to find Chloe to get to the truth, but it seems that the dark secrets in their community may be far more dangerous than she could ever have believed.